Analisis Kualitas Pelayanan Pengaduan Online Melalui Sistem Whatsapp Peduli Wong Cilik Di Dinas Sosial Kabupaten Sidoarjo - Devy Pramudiana, Ika; Arinda, Tata Novia; Kamariyah, Sri (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2024)
Si Whapik is a service system through WhatsApp for all types of services provided by the Sidoarjo Regency Social Service, if residents experience problems in using other service applications, such as Si Praja, or cannot take care of directly to the Social Service due to emergency conditions, by sending document files through whatsApp. This study aims to explore the analysis and obstacles that arise during the complaint service process through Si Whapik available at the Sidoarjo Regency Social Service. The research method applied is a qualitative descriptive method, with data collection through interviews, observations, and documentation. The theory of public service quality using five service indicators, namely: Tangible, Reability, Assurance, Responsiveness, and Emphaty is used as a reference framework for data collection. The results of the study show that the complaint service through Si Whapik at the Sidoarjo Regency Social Service has been fulfilled with the existence of complaint services through Si Whapik people do not need to go far to the Sidaorjo Regency Social Service to carry out services, but there are still obstacles experienced by Regency Social Service officers, namely in the facilities and infrastructure and the flow of complaint service mechanisms. However, the obstacles that arise in the complaint service process through Si Whapik can be overcome properly by the officers. This is an added value for Si Whapik's complaint service and at the same time contributes to improving the overall quality of service.